2012
DOI: 10.1175/jas-d-11-0163.1
|View full text |Cite
|
Sign up to set email alerts
|

Subgrid Model with Scaling Laws for Atmospheric Simulations

Abstract: Subgrid-scale parameterizations with self-similar scaling laws are developed for large-eddy simulations (LESs) of atmospheric flows. The key new contribution is the development of scaling laws that govern how these parameterizations depend on the LES resolution and flow strength. Both stochastic and deterministic representations of the effects of subgrid-scale eddies on the retained scales are considered. The stochastic subgrid model consists of a backscatter noise term and a drain eddy viscosity, while in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 49 publications
4
43
0
Order By: Relevance
“…The multi-field QDIA and its underpinning Langevin equation also provide further support for the direct stochastic modeling approach to subgrid-scale parameterizations developed by Frederiksen and Kepert [2] and applied also to the baroclinic QG equations for atmospheric and oceanic flows by Zidikheri and Frederiksen [32][33][34] and Kitsios, Frederiksen and Zidikheri [35]. In some of these studies, particularly for higher resolution LESs of atmospheric flows [32,33,35], where the baroclinic instability is resolved, the renormalized mean forcing is essentially just the bare forcing: ) , ( ) [34], the subgrid contribution to the mean field forcing is in general significant and the renormalized forcing is given by ) ,…”
Section: Concluding Commentsmentioning
confidence: 67%
See 3 more Smart Citations
“…The multi-field QDIA and its underpinning Langevin equation also provide further support for the direct stochastic modeling approach to subgrid-scale parameterizations developed by Frederiksen and Kepert [2] and applied also to the baroclinic QG equations for atmospheric and oceanic flows by Zidikheri and Frederiksen [32][33][34] and Kitsios, Frederiksen and Zidikheri [35]. In some of these studies, particularly for higher resolution LESs of atmospheric flows [32,33,35], where the baroclinic instability is resolved, the renormalized mean forcing is essentially just the bare forcing: ) , ( ) [34], the subgrid contribution to the mean field forcing is in general significant and the renormalized forcing is given by ) ,…”
Section: Concluding Commentsmentioning
confidence: 67%
“…Baroclinic oceanic flows were considered by Zidikheri and Frederiksen [33,34]; they applied the stochastic modeling approach and showed that it can be successfully used to maintain the correct LES spectra for both simple flows and more complex flows characteristic of the Antarctic circumpolar current. In very recent work, Kitsios, Frederiksen and Zidikheri [35] derived universal scaling laws for subgrid models of eddy-eddy interactions applicable to baroclinic atmospheric flows.…”
Section: [ ]mentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, at sufficiently high resolutions of the LESs, the off-diagonal elements of the aforementioned matrices became less important in magnitude compared with the diagonal elements. Recently, Kitsios et al [50,51] showed that universal scaling properties can be obtained for these parametrizations, making them applicable to a wide range of flows.…”
Section: (D) Stochastic Subgrid Modellingmentioning
confidence: 99%